2012
DOI: 10.1088/0741-3335/54/9/095010
|View full text |Cite
|
Sign up to set email alerts
|

Non-statistical population distributions for hydrogen beams in fusion plasmas

Abstract: Most atomic models for neutral hydrogen beams in fusion plasmas assume a statistical (Boltzmann) distribution of populations for excited states with the same principal quantum number n. Here we analyze population distributions for the excited magnetic sublevels of a beam under typical conditions of existing and future fusion devices. The collisional-radiative model NOMAD based on completely m-resolved parabolic states up to n = 10 is used to study this problem. The model utilizes new proton-impact excitation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…This allows us to only consider transitions between different energy levels. However, this assumption has been shown 26 to break down when the electron density is less than 10 14 cm À3 . In this regime, the following collisional radiative model can overestimate the D-a emission by about 20%-25%.…”
Section: Appendix: Collisional Radiative Modelmentioning
confidence: 99%
“…This allows us to only consider transitions between different energy levels. However, this assumption has been shown 26 to break down when the electron density is less than 10 14 cm À3 . In this regime, the following collisional radiative model can overestimate the D-a emission by about 20%-25%.…”
Section: Appendix: Collisional Radiative Modelmentioning
confidence: 99%
“…Thus, knowing the local density, these ratios are obtained from atomic model based relative intensity curves for an attenuated beam [27]. Although ratios from another model have been considered [28], it was found that the standard deviation of the differences between measured and predicted values of |B Z 2 + B φ 2 | 1/2 and ϕ are slightly larger for the latter ratios, hence the ratios from [27] are used here. Note: the -and + intensities, I − and I + respectively, are allowed to differ by a few percent as asymmetries can arise from beam divergence and beam width effects [17].…”
Section: Spectrum Fittingmentioning
confidence: 99%
“…A new general method was developed in Refs. [17,18] and is brieÀy described here. The major dif¿culty in calculation of collisional characteristics is due to presence of two independent quantization axis.…”
Section: Atomic Data For Mse and Bes Diagnosticsmentioning
confidence: 99%